The Use of GIS in Forensic Archaeology to Search Clandestine Graves in Uruguay - López Batista, Matías; Rodríguez López, Sofía; Fieguth Batista, Annika (​Forensic Archaeology, Anthropology and Ecology, 2021)
In the context of the search of detainee disappeared from the dictatorship occurred in Uruguay, forensic archaeology uses GIS as an auxiliary tool which allows to create, edit, visualize, store, analyse and publish geospatial data and information related to the investigation process. The tools of GIS are described in this article to show the results and information obtained which are going to be useful in the analytic processes leading to the design of new search strategies and archaeological intervention according to the available resources for this context. Two case studies are presented with the purpose to show the use of QGIS as a result of the three main areas of work: preliminary, fieldwork and laboratory. QGIS is presented as one of the most versatile, dynamic and accessible tool to investigate the search of detainee disappeared in Uruguay.